New Insights into the Hypotensins from Tityus serrulatus Venom: Pro-Inflammatory and Vasopeptidases Modulation Activities - Bruno Duzzi; Cristiane Castilho Fernandes Silva; Roberto Tadashi Kodama; Daniela Cajado-Carvalho; Carla Cristina Squaiella-Baptistão; Fernanda Calheta Vieira Portaro (Toxins, 2021)
The Tityus serrulatus scorpion is considered the most dangerous of the Brazilian fauna due to the severe clinical manifestations in injured victims. Despite being abundant components of the venom, few linear peptides have been characterized so far, such as hypotensins. In vivo studies have demonstrated that hypotensin I (TsHpt-I) exerts hypotensive activity, with an angiotensin-converting enzyme (ACE)-independent mechanism of action. Since experiments have not yet been carried out to analyze the direct interaction of hypotensins with ACE, and to deepen the knowledge about these peptides, hypotensins I and II (TsHpt-II) were studied regarding their modulatory action over the activities of ACE and neprilysin (NEP), which are the peptidases involved in blood pressure control. Aiming to search for indications of possible pro-inflammatory action, hypotensins were also analyzed for their role in murine macrophage viability, the release of interleukins and phagocytic activity. TsHpt-I and -II were used in kinetic studies with the metallopeptidases ACE and NEP, and both hypotensins were able to increase the activity of ACE. TsHpt-I presented itself as an inhibitor of NEP, whereas TsHpt-II showed weak inhibition of the enzyme. The mechanism of inhibition of TsHpt-I in relation to NEP was defined as non-competitive, with an inhibition constant (Ki) of 4.35 μM. Concerning the analysis of cell viability and modulation of interleukin levels and phagocytic activity, BALB/c mice’s naïve macrophages were used, and an increase in TNF production in the presence of TsHpt-I and -II was observed, as well as an increase in IL-6 production in the presence of TsHpt-II only. Both hypotensins were able to increase the phagocytic activity of murine macrophages in vitro. The difference between TsHpt-I and -II is the residue at position 15, with a glutamine in TsHpt-I and a glutamic acid in TsHpt-II. Despite this, kinetic analyzes and cell assays indicated different actions of TsHpt-I and -II. Taken together, these results suggest a new mechanism for the hypotensive effects of TsHpt-I and -II. Furthermore, the release of some interleukins also suggests a role for these peptides in the venom inflammatory response. Even though these molecules have been well studied, the present results suggest a new mechanism for the hypotensive effects of TsHpt-I